WHEN TEACHERS ARE DIGITAL: ISLAMIC EDUCATION, ARTIFICIAL INTELLIGENCE, AND IBN SĪNĀ’S ANXIETY - Maulidia, Martarosa; Finetri, Mahdaro; Fahmi, Muhammad (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2025)
The development of Artificial Intelligence (AI) technology has brought significant changes to the world of education, including Islamic education in Indonesia. The presence of AI as a digital teaching entity raises concerns about the future of human teachers, especially in terms of character building and the spirituality of students. This study aims to analyze the relevance of the existence of human teachers in the context of Islamic education disrupted by AI, by referring to the concept of wujūd and māhiyyah from Ibn Sīnā’s philosophy. This study uses a qualitative approach through literature study, with primary data in the form of the text of al-Shifā’ by Ibn Sīnā and secondary data from national and international accredited journals. The theory of wujūd and māhiyyah is used as a framework to evaluate the existence of AI as a “teacher”. The results of the study show that AI only has a functional existence without spiritual substance, so it does not qualify as an educational entity from the perspective of Islamic education. Human teachers, according to Ibn Sīnā, have māhiyyah that includes spiritual and moral dimensions that AI does not have. The conclusion of this study confirms that although AI can act as a tool, the role of teachers remains irreplaceable in shaping the souls and characters of students. Therefore, future Islamic education must develop a collaborative model that places AI as a partner, not a substitute for teachers.